PENCEGAHAN KECELAKAAN KERJA BERBASISHUMAN AND TECHNICAL APPROACH DI PURWOKERTO UTARA - Suryanto Suryanto; Anam A; Andodo C (Kesmas Indonesia, 2016)
Workplace accidents occur due to human error factor is unsafe behavior (85%). Accidents that often occur in small trader is burned by fire, hot water and cuts.Approach to human intervention (Human approach) is done via the safety behavior training, training, accident prevention, treatment of burns (combustio) and advocacy (advocacy). Engineering approach (technical approach) with training techniques safe electrical network installation and electrical wiring observation in the workplace. After participants attended further training of observation and advocacy in the workplace. Samples were selected by purposive sampling was small traders with the number of 40 people. Before and after the intervention pre-post test. Data was analyzed using the Wilcoxon test.Characteristics of the basic education level of respondents 14 people (35%), secondary education 26 people (65%). The majority of respondents have 1-3 years of work experience during which 21 people (52.5%). Participants who had experienced occupational accidents within the last 2 years was 29 (72.5%) and the rest have never had an accident. After participants attended training accident prevention there is an increase in the average value of respondents' awareness of workplace accidents between before training (pretest) and after training (posttest I) is from 13.3250 12.5250 become. Wilcoxon test results obtained by value p = 0.001 (<0.05) means that there are differences in knowledge about occupational accidents at small vendors between before (pretest) and after training (postest I).